Therapeutic benefit of combining calorie-restricted ketogenic diet and glutamine targeting in late-stage experimental glioblastoma - Mukherjee, Purna (Commun Biol, 2019)
Glioblastoma (GBM) is an aggressive primary human brain tumour that has resisted effective therapy for decades. Although glucose and glutamine are the major fuels that drive GBM growth and invasion, few studies have targeted these fuels for therapeutic management. The glutamine antagonist, 6-diazo-5-oxo-L-norleucine (DON), was administered together with a calorically restricted ketogenic diet (KD-R) to treat late-stage orthotopic growth in two syngeneic GBM mouse models: VM-M3 and CT-2A. DON targets glutaminolysis, while the KD-R reduces glucose and, simultaneously, elevates neuroprotective and non-fermentable ketone bodies. The diet/drug therapeutic strategy killed tumour cells while reversing disease symptoms, and improving overall mouse survival. The therapeutic strategy also reduces edema, hemorrhage, and inflammation. Moreover, the KD-R diet facilitated DON delivery to the brain and allowed a lower dosage to achieve therapeutic effect. The findings support the importance of glucose and glutamine in driving GBM growth and provide a therapeutic strategy for non-toxic metabolic management.